2018
DOI: 10.3390/s18103202
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infantile Movement Disorders in Video Data Using Deformable Part-Based Model

Abstract: Movement analysis of infants’ body parts is momentous for the early detection of various movement disorders such as cerebral palsy. Most existing techniques are either marker-based or use wearable sensors to analyze the movement disorders. Such techniques work well for adults, however they are not effective for infants as wearing such sensors or markers may cause discomfort to them, affecting their natural movements. This paper presents a method to help the clinicians for the early detection of movement disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
(92 reference statements)
0
26
0
Order By: Relevance
“…Nevertheless, it must be emphasized that the method was evaluated on a very small dataset. Khan et al [ 102 ] proposed a method for monitoring infants at home. They collected RGB data of 10 subjects using an additional RGB camera included in Microsoft Kinect.…”
Section: Methodology Of the Reviewed Approachesmentioning
confidence: 99%
“…Nevertheless, it must be emphasized that the method was evaluated on a very small dataset. Khan et al [ 102 ] proposed a method for monitoring infants at home. They collected RGB data of 10 subjects using an additional RGB camera included in Microsoft Kinect.…”
Section: Methodology Of the Reviewed Approachesmentioning
confidence: 99%
“…The authors in Reference [13] concluded that the selection of kernel function in SVM along with the optimal values of hyperparameters plays a critical role concerning the data. The authors in Reference [47] have also used SVM as a classification tool in their research. Yazdansepas et al [48] proposed a method to recognize the human activities of 77 subjects.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…However, as highlighted in [17], monitoring each limb individually is crucial to assist clinicians in the health-assessment process. With such a view, in [18] RGB images are processed to detect infant's limb skeleton with a learning-based approach. The histogram of oriented gradients is used as feature to train a structured support vector machine aimed at retrieving limb joints, which are then connected knowing the spatial relations between infants' body parts.…”
Section: A Related Workmentioning
confidence: 99%